Systematic review of interventions to increase the use of arteriovenous fistulae and grafts in incident haemodialysis patients. Issue 5 (September 2022) - De Siqueira, Jonathan; Jones, Alexander; Waduud, Mohammed; Troxler, Max; Stocken, Deborah; Scott, David Julian A
Background: Patients who commence haemodialysis (HD) through arteriovenous fistulae and grafts (AVF/G) have improved survival compared to those who do so by venous lines. Objectives: This systematic review aims to assimilate the evidence for any strategy which increases the proportion of HD patients starting dialysis through AVF/G. Data sources: Medline, Embase, Cochrane Central and Scopus. Study eligibility, participants and interventions: English language studies comparing any educational, clinical or service organisation intervention for adult patients with end stage renal failure and reporting incident AVF/G use. Study appraisal and synthesis: Two reviewers assessed studies for eligibility independently. Outcome data was extracted and reported as relative risk. Reporting was performed with reference to the PRISMA statement. Results: Of 1272 studies, 6 were eligible for inclusion. Studies varied in design and intervention. Formal meta-analysis was not appropriate. One randomised controlled trial and two cohort studies assessed the role of a renal access coordinator. Two cohort studies assessed the implementation of qualitive initiative programmes and one cohort study assessed a national, structured education programme. Results between studies were contradictory with some reporting improvements in incident AVF/G use and some no significant difference. Quality was generally low. Conclusions: It is not possible to reach firm conclusions nor make strategic recommendations. A comprehensive package of care which educates and identifies patients approaching dialysis in a timely manner may improve incident AVF/G use. An unbiased, robust comparison of different strategies for timing AVF/G referral is required.